Muatan HAM dalam Kebijakan Pendidikan Studi Evaluasi di Kota Yogyakarta - , Sofian Munawar; , Prof. Dr. M. Mohtar Mas'oed ([Yogyakarta] : Universitas Gadjah Mada, 2011)
âHuman rights content in education policy at the city of Yogyakarta is still in problematic! " This is the main finding of this study. Yogyakarta achievement in education was recognized by many parties have been very good. The informants in this study also confirm that. In terms of education policy, the informants of this study to assess the state-run education regulations Yogyakarta city have been very good, even to say progressive. However, when used as a human rights perspective to evaluate the parameters, rules-run education in the city of Yogyakarta is not good because it can be said still leaves a number of problems, especially with regard to three basic principles of the right to education which many allegedly violated in a number of existing education legislation, namely the principle of equality, non-discrimination, and state responsibility. In the third case the informants of this study is to assess the staterun education regulation of Yogyakarta is still weak. In the context of human rights, although no products of local legislation that specifically regulates human rights in the context of education policy, but the charge of human rights implicitly or explicitly in the legislation widely spread in the city of Yogyakarta. However, in the fifth aspect of the basic right to education â1) Guarantee of free primary education, 2) guarantee of compulsory education for primary education, 3) Guarantee literacy